Magnetization reversal of ferromagnetic nanoparticles under inhomogeneous magnetic field - Chang, Joonyeon; Yi, Hyunjung; Koo, Hyun Cheol; Mironov, V. L.; Gribkov, B. A.; Fraerman, A. A.; Gusev, S. A.; Vdovichev, S. N. (ELSEVIER SCIENCE BV, 2007)
We investigated remagnetization processes in ferromagnetic natioparticles under inhomogeneous magnetic field induced by the tip of magnetic force microscope (MFM) in both theoretical and empirical ways. Systematic MFM observations were carried out on arrays of submicron-sized elliptical ferromagnetic particles of Co and FeCr with different sizes and periods. It clearly reveals the distribution of remanent magnetization and processes of local remagnetization. of individual ferromagnetic particles. Modeling of remagnetization processes in ferromagnetic nanoparticles under magnetic field induced by MFM probe was performed on the base of Landau-Lifshitz-Gilbert equation for magnetization. MFM-induced inhomogeneous magnetic field is very effective to control the magnetic state of individual ferromagnetic nanoparticles as well as to create different distribution of magnetic field in array of ferromagnetic nanoparticles. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: SUPERCONDUCTING THIN-FILMS; JOSEPHSON-JUNCTIONS; CO DOTS; PARTICLES; ARRAYS; SYSTEM; TIP